Pengaruh Dana Zakat Infak dan Sedekah, Produk Domestik Regional Bruto dan Indeks Pembangunan Manusia Terhadap Kemiskinan Di Sulawesi Selatan - Muh. Syahidin; Abdul Rahman; A. Syathir Sofyan (AT TAWAZUN: Jurnal Ekonomi Islam, 2025)
This study aims to analyze the influence of Zakat, Infaq, and Alms (ZIS) Funds, Gross Regional Domestic Product (GRDP), Human Development Index (HDI), and the Covid-19 Dummy variable on poverty levels in South Sulawesi Province in the 2019-2023 period. This study uses a quantitative method with secondary data obtained from the South Sulawesi Central Statistics Agency (BPS) and the Baznas Institute. Data analysis was conducted using a panel data regression model with STATA software. The results show that ZIS Funds have an insignificant negative effect on poverty levels, confirming that effective fund distribution can help reduce poverty. GRDP also has an insignificant negative effect on poverty, indicating that increased economic activity directly improves people's living standards. HDI has a negative and significant effect on poverty, confirming the importance of investing in education, health, and a decent standard of living for poverty alleviation. Meanwhile, the Covid-19 Dummy variable has a positive and significant effect on poverty, indicating that the pandemic has had a substantial negative impact on people's welfare in South Sulawesi. This research provides practical implications for policymakers in designing integrated poverty alleviation strategies, including optimizing zakat management, increasing GRDP, and strengthening human resource quality. Therefore, the results are expected to serve as a reference in efforts to achieve inclusive and sustainable economic development.